Factors influencing public hospital nurses’ intentions to leave their current employment in Jordan - Al Momani, Mohammed (International Journal Of Community Medicine And Public Health, 2017)
Background: Shortage of nurses resulting from nurses migration, has created a health care crisis in developing countries and has adversely affected the quality of nursing care provided to patients. The main objective of this study was to investigate the factors influencing Jordanian public hospital nurses’ intent to leave their current employment. Methods: A cross-sectional survey was conducted among 348 registered nurses randomly selected from two public referral hospitals, Al Bashier Teaching Hospital, and Amirah Basma Teaching Hospital, Jordan. Data to investigate the nurses’ satisfaction and their intention to leave were collected using self-administered questionnaire compromised 28 factors included in seven dimension: Administrative support, supervision and leadership, interaction with co-workers, work related factors, staff development practices, pay and promotion system, and control and responsibility. Data collected over a 4-month period (December 13, 2015 to April 7, 2016). Results: of the 348 registered nurses 212 (60.9%) had an intention to leave their current work. The average satisfaction rate for all dimensions was (2.83). The dominant factors were not satisfied nurses (mean<3) and influencing their intention to leave were Pay and benefits, nurse to bed ratio due to shortage of nurses, and praising and recognitions for achievement. The variables gender, work experience, and nursing role yielded significant associations with intent to leave (p<0.05). Conclusions: The study showed that the majority of nurses were dissatisfied and had intention to leave their current job. Developing strategies to increase retention of nurses such as salaries and benefits should be periodically reviewed in light of the national consumer index, in addition to other strategies could improve nursing retention and quality of nursing care.